2018
DOI: 10.1002/bmc.4284
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in intestinal microbiota affect metabolism of ginsenoside Re

Abstract: Ginsenoside Re, an active ingredient in Panax ginseng, is widely used as a therapeutic and nutriment. The intestinal microbiota plays crucial roles in modulating the pharmacokinetics and pharmacological actions of ginsenoside Re. The aim of this study was to explore the relationship between bacterial community variety and the metabolic profiles of ginsenoside Re. We developed two models with intestinal dysbacteriosis: a pseudo-germ-free model induced by a nonabsorbable antimicrobial mixture (ATM), and Qi-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Another non-pharmacological approach is the oral administration of ginseng that has been shown to have anti-fatigue properties in ME/CFS, cancer-related fatigue and MS-related fatigue in several blinded randomizedcontrolled studies (34)(35)(36)(37). Just recently, it was suggested that the related pharmacokinetics are mediated via the gut microbiome (278,279). While these indications are all indirect and thus cannot be considered conclusive, even though randomized controlled trials are considered relatively strong evidence, they support the general principle of effective fatigue reduction accompanying changes to the gut microbiome in similar conditions, which makes assessment of whether the same applies in the ME/CFS setting relevant to test further.…”
Section: Other Potentially Gut Microbiome Mediated Approachesmentioning
confidence: 99%
“…Another non-pharmacological approach is the oral administration of ginseng that has been shown to have anti-fatigue properties in ME/CFS, cancer-related fatigue and MS-related fatigue in several blinded randomizedcontrolled studies (34)(35)(36)(37). Just recently, it was suggested that the related pharmacokinetics are mediated via the gut microbiome (278,279). While these indications are all indirect and thus cannot be considered conclusive, even though randomized controlled trials are considered relatively strong evidence, they support the general principle of effective fatigue reduction accompanying changes to the gut microbiome in similar conditions, which makes assessment of whether the same applies in the ME/CFS setting relevant to test further.…”
Section: Other Potentially Gut Microbiome Mediated Approachesmentioning
confidence: 99%
“…At genus level, the abundance of Parabacteroides , unidentified Saprospiraceae , and Elizabethkingia in Bacteroidetes were increased and Arcobacter, Marinobacter , Alkanindiges, Sulfuricurvum, Haliangium, and Thiobacillus belonging to Proteobacteria were decreased in YZXJ group. A large amount of data confirmed that Bacteroides can promote the metabolism of ginsenoside that indirectly improves the state of physical fatigue [64, 65]. Proteobacteria mainly include Helicobacter and Shigella , both of them can promote the occurrence of CRC by inducing inflammatory reaction and also play an important role in causing CRF [6668].…”
Section: Discussionmentioning
confidence: 99%
“…As a class of glycoside compounds, the ginsenosides in ginseng drugs after oral administration can be largely transformed by the gut microorganism, and the obtained metabolites together with the prototype compounds are absorbed. Identification of the in vitro (co-cultured with the intestinal flora from healthy human or animals, 327–330 or rat liver microsomes 331 ) and in vivo metabolites (from the healthy human or animal plasma, urine, bile, feces or zebrafish 332–341 ) of ginsenosides was performed by LC-MS. Information on the identified metabolites for the ginsenoside analytes has been given in Table S7 † 327–340,342–344 . In general, the hydrophilic ginsenosides are metabolized to hydrophobic compounds by gastric juices and gut microbiota: (1) the PPD-type ginsenosides are mainly transformed into compound K (CK) and Rh2; (2) the PPT-type to Rh1 and the PPT sapogenin; (3) the OT-type to ocotillol.…”
Section: Metabolism and Metabolomicsmentioning
confidence: 99%
“…332 The feces of rats after the administration of Re were analyzed and 10 metabolites were detected and identified, three of which were new compounds. 340 The metabolites of noto-R1, Rg1, and Rb1 in zebrafish were studied by HPLC-ESI-MS, and deglycosylated metabolites and hydroxylation metabolites of these three saponins were identified. 335…”
Section: Metabolism and Metabolomicsmentioning
confidence: 99%